Kerangka Regulasi Ekspor Usaha Mikro, Kecil, dan Menengah Melalui Marketplace Internasional dan Implikasinya terhadap Penerimaan Negara di Indonesia: Regulatory Framework for Micro, Small, and Medium Enterprises Exports Through International Marketplaces and Its Implications for State Revenue in Indonesia - Rhino Aldy Herlambang; Raff Justin Abraham Siahaan; Sandya Tristan Simbolon; Raffaello Emmanuel Jungjunan (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2026)
Digital transformation has reshaped international trade through the emergence of digital platforms, creating new export opportunities for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of international digital platforms in facilitating MSME exports from the perspectives of international trade law and public finance law. This research employs a normative legal method using statutory and conceptual approaches based on secondary data. The findings indicate that digital platforms expand market access for MSMEs but also give rise to legal challenges, including issues related to digital jurisdiction, platform accountability, and the taxation of cross-border digital transactions. This study finds that Indonesia's regulatory framework remains fragmented in governing MSMEs' digital exports, particularly with respect to taxation nexus, platform accountability, and jurisdictional enforcement. Therefore, harmonization of digital trade and tax regulations, along with strengthened international cooperation, is necessary to optimize state revenue generated from MSMEs' digital export activities. Therefore, it is necessary to reform regulations governing digital trade and taxation, as well as strengthen international cooperation, in order to optimize state revenue generated from MSMEs' digital exports.